Հակոբ Պարոնյանը և իր ժամանակը - Ա. Մ. Գլջյան (ՀՀ ԳԱԱ հրատ.)
Պարոնյանի մեծությունը մեկնաբանելիս քննադատներն ընդգծել են միայն նրա երգիծական տաղանդը, իսկ միջավայրի դրական ազդեցությունը ստեղծագործական անհատականության վրա մերժել են։ Рассматривая знаковость личности и творчества Акопа Пароняна, критики фокусируют свое внимание лишь на его врожденном сатирическом таланте, не учитывая позитивное влияние среды на творческую ин-дивидуальность писателя. Considering the significance of the personality and creativity of Hakob Paronyan, critics focus their attention only on his innate satirical talent, not taking into consideration positive influence of the environment on the writer's creative individuality.
Keywords: Literature; Auxiliary Sciences of History; Language and Literature; Biography